The future of protein feed: a case study of sustainable substitutes in the German livestock industry - Sakson Soisontes; Florian Freund; Verena Laquai (Environment, Development and Sustainability, 2023)
The use of imported soybean/soybean meal is criticized in the context of the sustainability discussion in Germany. Imported soybean is often associated with deforestation and genetic modification, which is largely viewed critically by consumers. This study aims to forecast changes in future demand for imported soybean/soybean meal and its possible substitutes in the German livestock industry. The two-round Delphi method was used in the study by sending questionnaires to 28 experts from four groups: food retailers, livestock associations, animal nutrition manufacturers and research institutes. Our main result is that the total use of soybeans in German livestock farming will decrease from almost 4 million tons of soybean equivalents in 2018/19 to approximately 3.4 million tons by 2030/31. In contrast, the share of non-GM soybean is forecast to increase from 26 to 53%. Factors that influence the increased use of non-GM protein feeds most are "specifications from downstream processors" and "demand from the feed industry." Experts forecast that about 36% of imported soybean/soybean meal (from non-EU countries) for German livestock farming could be replaced by protein feed produced in the EU. Rapeseed was considered to have a particularly high potential for production in the EU, followed by soybean and sunflower. Experts considered the factors: "requirements by the food retailers," "reasonable price," "political regulation" and "better profitability for the producer" as the most influential for extended use of regional protein feeds.
Keywords: 330; Non-GM soybean; Regional protein feeds; Food retailers; Two-round Delphi; Sustainability